Analysis of the heterogeneity of the chemical composition of snow cover using clustering methods (k-means) and GIS-technolog - A. V. Zakharchenko; D. V. Moskovchenko; A. A. Tigeev (Лëд и снег, 2022)
The purpose of the work is a comparative analysis of the geochemical spectra of melt water and dust in the snow cover of the city of Tyumen and its surroundings. Sampling was carried out in 2020 using standard methods. Content of macro-elements (Na, Mg, Al, P, S, K, Ca, Fe, Mn) was determined by the ICP-AES atomic emission method (iCAP-6500, Thermo Scientific, USA), microelements – by mass spectrometry with inductively coupled plasma ICP- MS (X-7 Thermo Elemental, USA). The main method of analyzing the inhomogeneity of the territory was multidimensional cluster analysis (k-means). If sampling points have a high (or low) content of individual chemical elements, but are located among the points with lower (or higher) content, then the problem of formation of them arises. The problem points of water-soluble macro-elements have a high content of Na, Ca and Mg that results from the use of different anti-icing reagents. Macro-elements of the solid phase of snow are mostly similar in composition to background soils; the problem points are more often found in the northern part of the city, however some of them may be observed in other sites. According to the geochemical spectrum, microelements of the liquid phase of the snow cover are divided into four clusters. Background cluster С1 is located at the maximum distance (20–35 km) from the city center. It is distinguished by higher contents of Ni, Cu, Pb, Li, Sn, W relative to the background cluster С2. The cluster С2 has the lowest content of microelements and combines some points of the background also in the central part of the city. Cluster С3 (2 points) is located in the industrial area. By the composition of microelements, the cluster С4 has a geochemical spectrum similar to the С2 cluster, but with a higher content of them. According to the content of microelements in the solid phase, the C1 cluster combines the background and partly urban areas. Clusters С2 and С3 are similar in geochemical spectrum, but differ in the content of heavy metals. Geographically, they tend to the northern part of the city. Problem points are notable in cluster C4. They are located far from the industrial zone and main roads. Their localization may be caused by the precipitation of snow dust from the atmosphere during its regional transport.